The MexTAg collaborative cross: host genetics affects asbestos related disease latency, but has little influence once tumours develop - Fisher, Scott A.; Patrick, Kimberley; Hoang, Tracy; Marcq, Elly; Behrouzfar, Kiarash; Young, Sylvia; Miller, Timothy J.; Robinson, Bruce W. S.; Bueno, Raphael; Nowak, Anna K.; Lesterhuis, W. Joost; Morahan, Grant; et al. (Frontiers in Toxicology, 2024)
Objectives: This study combines two innovative mouse models in a major gene discovery project to assess the influence of host genetics on asbestos related disease (ARD). Conventional genetics studies indicate that some susceptibility to mesothelioma is genetic. However, the identification of host modifier genes, their roles and whether they contribute to disease remain unknown. Here we report a study designed to rapidly identify genes associated with mesothelioma susceptibility by combining the Collaborative Cross (CC) and the well-characterised MexTAg mesothelioma mouse models. Methods: The CC is a powerful mouse resource that harnesses over 90% genetic variation in the mouse species, allowing rapid identification of genes mediating complex traits. MexTAg mice rapidly, uniformly, and predictably develop mesothelioma, but only after asbestos exposure. To assess the influence of host genetics on ARD, we crossed 72 genetically distinct CC mouse strains with MexTAg mice and exposed the resulting CC-MexTAg (CCMT) progeny to asbestos and monitored traits including overall survival, ARD latency, ARD onset progression and ascites volume. We identified phenotype-specific (trait) associated modifier genes and validated the role of human orthologues in asbestos-induced carcinogenesis using human mesothelioma datasets. Results: We observed considerable variation in overall survival and disease latency in asbestos exposed CCMT mice. Surprisingly, however, there was no variation in disease progression, demonstrating that host genetic factors do have a significant influence during disease latency but have a limited role once disease is established. Quantitative trait loci (QTL) affecting ARD survival/latency were identified on chromosomes 6, 12 and X. Of the 97-protein coding candidate modifier genes that spanned these QTL, eight genes (CPED1, ORS1, NDUFA1, HS1BP3, IL13RA1, LSM8, TES and TSPAN12) were found to significantly affect outcome in both CCMT and human mesothelioma datasets. Conclusion: Host genetic factors affect susceptibility to development of asbestos associated disease. However, following mesothelioma establishment, genetic variation in molecular or immunological mechanisms did not affect disease progression. Identification of multiple candidate modifier genes and their human homologues with known associations in other advanced stage or metastatic cancers highlights the complexity of ARD and may provide a pathway to identify novel therapeutic targets.